2021
DOI: 10.1016/j.scitotenv.2021.146270
|View full text |Cite
|
Sign up to set email alerts
|

Can shellfish be used to monitor SARS-CoV-2 in the coastal environment?

Abstract: The emergence and worldwide spread of SARS-CoV-2 raises new concerns and challenges regarding possible environmental contamination by this virus through spillover of human sewage, where it has been detected. The coastal environment, under increasing anthropogenic pressure, is subjected to contamination by a large number of human viruses from sewage, most of them being non-enveloped viruses like norovirus. When reaching coastal waters, they can be bio-accumulated by filter-feeding shellfish species such as oyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 65 publications
2
50
0
1
Order By: Relevance
“…A recent monitoring study made in several sites along the coast of France reported the absence of SARS-CoV-2 in oysters (Desdouits et al, 2021). The authors, nonetheless, do not exclude shellfish as potential agents of transmission, but highlight the need for more monitoring studies before reaching such conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…A recent monitoring study made in several sites along the coast of France reported the absence of SARS-CoV-2 in oysters (Desdouits et al, 2021). The authors, nonetheless, do not exclude shellfish as potential agents of transmission, but highlight the need for more monitoring studies before reaching such conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the possible toxicity of raw wastewater, causing an advanced dissection of organisms exposed to the most concentrated raw sewage conditions (18% of samples during the exposure at the end of September and 26% of samples during the last exposure, in November), did not allow mussels to be exposed any longer. To dispense with the toxicity of raw wastewater, a longer exposure of the mussels (from 14 to 21 days) in the laboratory to a noninfectious SARS-CoV-2 or to low pathogenic CoV strains could improve characterization of virus accumulation within mussels (Desdouits et al, 2021;Wurtzer et al, 2020b).…”
Section: Zebra Mussels As Biological Indicators Of Water Contamination By the Sars-cov-2 Genomementioning
confidence: 99%
“…or in countries whose water treatment structures are still underdeveloped. As announced by several recent studies, the bivalve taxon represents a complementarity, even a more than plausible alternative for the detection of viruses in the environment (Capizzi-Banas et al, 2021;Desdouits et al, 2021;La Rosa et al, 2021;Polo et al, 2021). Various fields of application can therefore be envisaged, such as 486 environmental biomonitoring for health purposes.…”
Section: Zebra Mussels As Biological Indicators Of Water Contamination By the Sars-cov-2 Genomementioning
confidence: 99%
See 2 more Smart Citations